Складання тексту юридичного документа: методичні вказівки - Довгополова, Г. Г.; Dovhopolova, H. H.; Василенко, В. А.; Vasylenko, V. A.; Г.Г. Довгополова; Валентина Василенко (Актуальнi питання гуманiтарних наук. - 2024. - Вип. 73, т. 1. - С. 232-235, 2024)
Зазначено, що належне складання юридичних документів є важливим для забезпечення ясності, примусового виконання та захисту прав. Якісно складені юридичні документи зводять до мінімуму можливі суперечки та створюють міцну основу для правових відносин. Розглянуто ключові аспекти щодо складання юридичних документів.

The article will be useful to students of legal education who seek to improve their skills in drafting legal documents. The language of law should contribute to the creation of effective and accurate legal texts. Legal documents, with their complex language and formal structure, can often seem overwhelming even to those with a legal background. However, understanding how to draft these important documents is a skill that can be developed in every practitioner. Well-drafted legal documents minimize potential disputes and create a solid foundation for legal relationships. This article discusses the key aspects of drafting legal documents. First, it is an understanding of the purpose of drafting the document. The choice of terminology, the method of construction and rhetoric in general will depend on this. You can customize the document to suit your specific needs by defining a purpose. The next step is to define the parties involved and their roles. Understanding their roles is critical to defining the obligations, rights and responsibilities that should be addressed in the document. Researching the applicable laws and regulations is an important step. In order to create a legally sound document, it is extremely important to conduct thorough legal research, familiarize yourself with the laws and regulations related to the topic of your document. Only after that you can begin to outline the structure and sections of the actual document. Creating a clear and logical structure is critical to organizing the content of a legal document. This step determines the order of the table of contents and main headings to ensure a logical flow and easy understanding. Effective organization of the document contributes to its readability and ease of use. Creating a draft document involves determining the tone and language tools that will be used in it. A clear, logical introduction that expresses the intentions and personalities of the parties involved plays an important role. It sets the tone and purpose of the document. Definitions of key terms should be included in the draft to avoid ambiguity and ensure common understanding. Clear definitions increase the clarity and interpretation of the document. The next steps suggested by the author of the article is a preliminary review and examination of the legal document. After the initial draft is completed, it is very important to review the document carefully, checking for consistency, accuracy and clarity of language, and whether there are any unclear or open to interpretation areas. Based on the lawyer’s recommendations, it is necessary to make the necessary changes and proposals to the document. This may involve revising language, adding or changing provisions, or reorganizing sections to ensure consistency and clarity, etc.

Отмечено, что надлежащее составление юридических документов важно для обеспечения ясности, принудительного исполнения и защиты прав. Качественно составленные юридические документы сводят к минимуму возможные споры и создают прочную основу правовых отношений. Рассмотрены ключевые аспекты составления юридических документов.
Composition of the text of a legal document: methodological instructions
Keywords: юридичний документ; мова права; юридичні терміни; оформлення документа; правовий текст; legal document; legal language; legal terms; document design; legal text; юридический документ; язык права; юридические термины; оформление документа; правовой текст